First maturation size for five species of fish in an area of the Amazon Coast Maranhense, Brazil (Research, Society and Development, 2021)
The present study aimed to determine the sizes of first sexual maturation of five commercial species of an area of the Maranhense Amazon Coast, to be used as an indicator in the fishing order in the region. The first gonadal maturation length (L50) of species: Bagre bagre, Lutjanus synagris, Macrodon ancylodon, Mugil curema and Trichiurus lepturus was estimated from the cumulative curve of frequencies of occurrence of adult individuals by class of total length adjusted to the logistic function. The first gonadal maturation lengths of B. bagre, L. synagris, M. ancylodon, M. curema and T. lepturus were 24.28 cm, 26.52 cm, 19.54 cm, 19.93 cm and 51.45 cm, respectively. Thus, it is suggested to avoid capturing, storage, disembarkation and sale of individuals smaller than the values presented in this study.